Defining the Self as Axiological Organization: An Enactive Approach to the Metaphysics of Personal Identity - Mocker, Grant (My University, 2022)
Enactivism builds on the “embodied turn” in cognitive science to firmly establish the close connection between mind and life, exemplified in the work of Evan Thompson. The more recent “interactive turn” emphasizes that individuals’ mental and cognitive processes are shaped by social interactions with other cognitive agents. Regarding personal identity, Miriam Kyselo argues that it remains unclear how and to what extent the self is individuated by these processes, and whether or not social relations are necessary for self-persistence. Further, it remains unclear how the self of simple biological organisms is continuous with the much more complicated personal identity of human beings, who are subject not only to the forces of the natural world, but also to forces that arise only in their uniquely symbolic and sociocultural milieu. I contend that we can come to understand how evaluations dependent on the individual’s needs and desires, what Charles Taylor refers to as “weak evaluations,” are continuous with “strong evaluations,” whose validity are independent of the individual’s needs and desires, by recognizing that some organisms not only create value, but respond to values already present in their environment. The general notion of selfhood that results is one of axiological organization. I argue that what we are really referring to with the term “self” is the organization of evaluations that organisms make in regard to environmental affordances, a system which, over time, comes to take on definitive traits and characteristics. The self, regardless of the particular context in which it is situated, becomes individuated by the evaluations it makes, and is experienced as persistent because evaluative activity is an on-going process, ending only in death. The self is further experienced as persistent because these evaluations are made in accordance with a critical standard which itself rarely, and the overall axiological organization retains a high degree of stability.
Keywords: Self; Personal Identity; Enactivism